Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae) - Brescovit, Antonio D.; Cizauskas, Igor (Zootaxa, 2019)
Seven new species of the spider genus Matta are described from caves in the State of Minas Gerais, Brazil: M. zuiuda sp. n., Matta pititinha sp. n., Matta humhum sp. n., Matta cambito sp. n., Matta humrrum sp. n., Matta nuusga sp. n., and Matta teteia sp. n. Among these seven species, six have morphological features consistent with specialization to the subterranean environment and we hypothesize that they are troglobites. One species, Matta zuiuda sp. n., shares morphology similar to M. hambletoni Crosby and M. angelomachadoi Brescovit which are known from surface populations in the State of Minas Gerais.